The Male Figure. (Los Angeles : Bruce of Los Angeles, 1956)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : 4 maal per jaar
Redactie : Box 75605, Sanford Station, Los Angeles 5, Calif. ; vanaf [?] 11768 Kensington Road Los Alamitos Calif. 90720
Engels
Periodiek